Fluorescence of intact human teeth enamel in vivo - Sarycheva, Iraida; Yanushevich, Oleg; Minakov, Dmitriy; Shulgin, Vladimir (Journal of Stomatology, 2015)
In this article the fluorescence of different anatomical areas of intact teeth of the upper and the lower jaw in vivo has been investigated. It was found that on average the enamel in cervical area has the highest fluorescence intensity and the enamel in the incisal edge area has the lowest. This fact is connected with the uneven homogeneity of enamel thickness, which depends on the anatomical area of a tooth and the influence of dentine-enamel junction and dentine layer on the overall fluorescence signal. To prove this hypothesis, enamel thickness in different anatomical areas of intact teeth has been measured using the methods of multilayer spiral computed tomography and scanning electron microscopy. The obtained results are very important for the investigation of mechanism of dental hard tissues fluorescence as well as for the prospective practical application of the method of laser-induced fluorescence to diagnostics of carious and non-carious lesions.